Contralesional arm preference depends on hemisphere of damage and target location in unilateral stroke patients - Mani, Saandeep (2014)
BACKGROUND: Previous research has shown that during simulated activities of daily living right handed stroke patients use their contralesional arm more after left than right hemisphere stroke. These findings were attributed to a hand preference effect. However, these decisions about when to use the contralesional arm may be modulated by where in the work space the task is performed, a factor that could be used in physical rehabilitation to influence recovery by decreasing learned non-use. OBJECTIVE: To examine how target location and side of stroke influences arm selection choices for simple reaching movements. METHODS: Fourteen right-handed stroke patients (7 with left hemisphere damage, 7 with right hemisphere damage) with similar degree of hemiparesis (Fugl-Meyer motor score), and 16 right-handed control subjects participated in this experiment. Thirty-two targets were presented throughout the reachable horizontal plane workspace in a pseudo-random fashion, and the subjects were asked to select one hand to reach the target on each trial. RESULTS: The left hemisphere damaged group chose their contralesional arm significantly more often than the right hemisphere damaged group. Patients with right hemisphere damage also chose their left (contralesional) arm significantly less than the control group. However, these patterns of choice were most pronounced in the center of the workspace. CONCLUSION: Both the side of hemisphere damage and workspace location played a significant role in the choice of whether to use the contralesional arm for reaching. These findings have implications for structuring rehabilitation for unilateral stroke patients.